Effect of time-to-surgery on in-house mortality during orthogeriatric treatment following hip fracture: A retrospective analysis of prospectively collected data from 16, 236 patients of the AltersTraumaRegister DGU®. Issue 3 (March 2021) - Schoeneberg, Carsten; Aigner, Rene; Pass, Bastian; Volland, Ruth; Eschbach, Daphne; Peiris, Shugirthanan Edwin; Ruchholtz, Steffen; Lendemans, Sven; ,
Highlights: Overall in-house mortality after geriatric hip fracture was 5.5%. The median age of the included patients was 85 years, and only patients aged 70 years or older were included. No significant differences regarding in-house mortality rate between the time-to-surgery intervals of 24 and 48 h or slightly above. Mortality indicators: ASA ≥ 3, fracture during hospital, ISAR ≥ 2, age, and male gender. Abstract: Background: Time-to-surgery in geriatric hip fractures remains of interest. The majority of the literature reports a significantly decreased mortality rate after early surgery. Nevertheless, there are some studies presenting no effect of time-to-surgery on mortality. The body of literature addressing the effect of an orthogeriatric co-management is growing. Here we investigate the effect of time-to-surgery on in-house mortality in a group of patients treated under the best possible conditions in certified orthogeriatric treatment units. Methods: We conducted a retrospective cohort registry analysis from prospectively collected data of the AltersTraumaRegister DGU®. Data were analyzed univariably, and the association of early surgery with in-house mortality was assessed with multivariable logistic regression while controlling for specified patient characteristics. Additionally, propensity score matching for time-to-surgery was applied to examine its effect on the in-house mortality rate. Findings: A total of 15, 099 patients met the inclusion criteria. The median age was 85 years (IQR 80–89), and 72.1% were female. The overall in-house mortality rate was 5.5%. Most (71.2%) of the patients were treated within 24 h, and 91.6% within 48 h. Neither the multivariable logistic regression model nor the propensity score matching indicated that early surgery was associated with a decreased mortality rate. The most important indicators for mortality were ASA ≥ 3 [Odds ratio (OR) 3.4, 95% confidence interval (CI) 2.35–5.11], fracture event during inpatient stay (OR 2.6, 95% CI 1.48–4.3), ISAR ≥ 2 (OR 1.88, 95% CI 1.33–2.76), and male gender (OR 1.71, 95% CI 1.39–2.09). Interpretation: Our results suggest that for those patients, who were treated in an orthogeriatric co-management under the best possible conditions, there are no significant differences regarding in-house mortality rate between the time-to-surgery intervals of 24 and 48 h or slightly above. This and the comparatively small number of patients who underwent surgery after 24 h show that an extension of the pre-surgery interval, justified by an orthogeriatric treatment team, will not be detrimental to the affected patients.